Berthoud Fire Protection District - Wildland Urban Interface - Colorado State Forest Service, compiler (Colorado State University. Libraries, 2006)
Located in: Fort Collins office files. Berthoud Fire Protection District's 2007 grant application to the Colorado Western States Wildland Urban Interface to develop a Wildland Fire Hazard and Risk Assessment and the resulting Healthy Forests Restoration Act (HFRA) compliant Community Wildfire Protection Plan.
Keywords: Colorado State Forest Service -- History -- Sources; Forests and forestry--Colorado